A complex chromosome rearrangement with 10 breakpoints: tentative assignment of the locus for Williams syndrome to 4q33----q35.1. Issue 4 (April 1992) - Tupler, R; Maraschio, P; Gerardo, A; Mainieri, R; Lanzi, G; Tiepolo, L
Abstract : An unbalanced complex chromosome rearrangement with 10 breakpoints resulting in four derivative chromosomes (1, 2, 4, and 11) was found in a girl with severe phenotypic abnormalities, many of which are characteristic of Williams syndrome. The patient was monosomic for the region 4q33----q35.1 and thus the mapping of the syndrome could tentatively be restricted to this region.